Cercarial development of Fasciola within the intermediate snail host Lymnaea acuminata from river waters of Aurangabad (M.S.) India - Nagare, K R; Dummalod, C B (Journal of Experimental Sciences, 2013)
Collection of snail specimens of Lymnaea acuminata was done from river water around the city Aurangabad. Naturally infected snails were identified and dissected in order to study the cercarial development within the snail body. Infected gonads were collected and got processed for general histological study in order to investigate cercarial development. Light microscopic observations of the gonadal sections show various stages of cercarial development within redia of liver fluke, Fasciola. Redia are formed after completion of the sporocyst development. Fully developed rediae are polymorphic shaped sacks having mouth opening at the anterior end. Just behind the collar region at one site there is presence of birthpore which acts as an exit for developing cercaria. From the germinal layer proliferation of germ balls take place vegetatively. At the initial stages of germball development, it is simple ball of cells. On further development it becomes elongated with mesenchyme tissue.Advancement in further development, there starts the formation of digestive system with distinct intestinal lobes or caecae. During post developmental stages there is appearance of pharynx, suckers and tail of cercaria. It seems that cercaria move towards anterior region with progress in their development. Fully developed cercaria having distinct tail gets birth through birthpore.